Qualidade física, química e microbiológica de ovos lavados armazenados sob duas temperaturas e experimentalmente contaminados com Pseudomonas aeruginosa - MENDES, Fernanda Rodrigues (2010)
The objective of this study to verify the physical, chemical and bacteriological egg-washed and not washed undergoing experimental infection with Pseudomonas aeruginosa and stored at 5 oC and 25 oC during the 30 days. We used 768 eggs without cracks and classified as large, hens line Dekalb White, 30 to 40 weeks of age, and 384 for physical and chemical quality and 384 for bacteriological quality. The experimental design was in blocks of two stages and in factorial 2 x 2 x 2 (contamination, washing and storage temperature) with six repetitions for variables of physical, chemical and bacteriological. Eggs were contaminated by handling, with 1.5 x 105 units forming colonies (CFU) of Pseudomonas aeruginosa / mL and remained 5c and stored at 25oC for 30 days. Every 10 days were analyzed physical quality of eggs (egg weight, specific gravity, thickness shell, yolk percentage, albumen and shell, Haugh unit, yolk index and albumen), chemistry (pH of albumen and yolk) and bacteriological (count bacteria on the shell and contents of the egg). To analyze the weight loss of eggs at 30 days were used 96 eggs weighed every three days. The experimental design was randomized blocks in factorial 2 x 2 x 2 (Contamination washing x x storage temperature), with six replicates and one egg per experimental unit. It was observed that the cooling maintained the internal egg quality even when there was contamination in shell with inoculum of Pseudomonas aeruginosa (p <0.05). It was concluded that the Refrigeration slows weight loss and provides better internal quality, physics, and chemistry of eggs during the 30 days of storage (p> 0.05), independent of the contamination and the washing process. Best values internal quality were obtained in chilled eggs (p <0.05), eggs stored at 5 ° C had lower bacterial counts (p <0.05). It was concluded that the cooling provides better quality of bacteriological eggs during 30 days of storage and that there was more growth bacterial washed eggs and especially the content of the eggs.